2017
DOI: 10.12795/elia.2017.i17.04
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the benefits of a metacognitive reading strategy instruction programme between CLIL and EFL primary school students

Abstract: Comparing the benefits of a metacognitive reading strategy instruction... (Wenden & Rubin, 1987;O'Malley & Chamot, 1990;Chamot & O'Malley, 1994;Cohen & Macaro, 2007;Chamot, 2008; Cohen, 2011, entre otros) han demostrado que el uso de las estrategias de aprendizaje produce un efecto positivo en el éxito de los hablantes aunque este campo no ha estado exento de controversia (Rees-Miller, 1993; Dörnyei y Skehan, 2003;Dörnyei, 2005;Manchón, 2008;Macaro, 2006Macaro, , 2007Macaro, , 2010 aim of this study is to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Metacognitive strategies are also essential in English reading, as noted by Muhid et al [43] in their study with 50 students showed significant results that metacognitive strategies had on reading performance, several strategies were worked on, but the most used was selective attention and the least used was self-reflection. In the same sense, Gutiérrez and Ruíz [44] investigated the effects of training in metacognitive reading strategies in two educational contexts of Spanish students, the group that carried out the strategic training obtained better scores, highlighting the importance of strategies in the understanding of The texts. Likewise, Reshadi-Gajan et al [45] to improve reading comprehension in English in Iranian students used a computerized RMSA system with significant results.…”
Section: Resultsmentioning
confidence: 99%
“…Metacognitive strategies are also essential in English reading, as noted by Muhid et al [43] in their study with 50 students showed significant results that metacognitive strategies had on reading performance, several strategies were worked on, but the most used was selective attention and the least used was self-reflection. In the same sense, Gutiérrez and Ruíz [44] investigated the effects of training in metacognitive reading strategies in two educational contexts of Spanish students, the group that carried out the strategic training obtained better scores, highlighting the importance of strategies in the understanding of The texts. Likewise, Reshadi-Gajan et al [45] to improve reading comprehension in English in Iranian students used a computerized RMSA system with significant results.…”
Section: Resultsmentioning
confidence: 99%
“…Through the use of focus group interviews, it is the learners that were in control of the research outcomes, not the researcher, as they compared their pre and post feedback writing drafts and were given time to reflect on whether the feedback affected their academic writing proficiency. Results were analyzed and triangulated, comparing the students' reflections and opinions with the writing rubric that focuses on the placement of a "thesis statement at the end of introduction, introducing paragraphs with topic sentences, including supporting ideas within the paragraphs, using logical transitions and connecting words between the paragraphs and the sentences (Martínez et al, 2017).…”
Section: Autonomymentioning
confidence: 99%
“…There are no doubts that perspectives of teaching English are enormous (Fry et al 2009;Moreno Rubio 2009;Ko et al 2014). Thus, among other studies, Bušljeta (2013) and Silva (2017) discuss audiovisual-cum-auditory materials and oral influences in phrases; while Martínez and De Zarobe (2017), and Liendo and Massi (2017) explore the metacognitive reading strategy and a didactic academic literacy, genre and competence models for EFL candidates. As George and Salgado-Robles (2018) and Kapranov (2018) consider teachersʼ beliefs and attitudes, and studentsʼ awareness of grammatical forms; so also Liddicoat (2019) and Alcaraz-Mármol (2019) examine intercultural appreciation and oral skill linguistic meditation as good teaching strategies.…”
Section: Introductionmentioning
confidence: 99%